(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
Through the steps of the history of medically assisted reproduction in Italy, that develops in an emblematic way among the law?maker, judges and Courts, the Author deals with the relationship between political law and case law in the protection of last generation fundamental rights.